Moving beyond threshold‐based dichotomous classification to improve the accuracy in classifying non‐responders - Bonafiglia, Jacob T. (Physiol Rep, 2018)
We examined maximal oxygen consumption responses following exercise training to demonstrate the limitations associated with threshold‐based dichotomous classification of responders and non‐responders and proposed alternative methods for classification. Specifically, we: 1) calculated individual probabilities of response, and 2) classified individuals using response confidence intervals (CI) and reference points of zero and a smallest worthwhile change of 0.5 METs. Our findings support the use of individual probabilities and individual CIs to improve the accuracy in non‐response classification.